OESTRUS SPECIFIC PROTEINS FROM SALIVA AND CERVICO VAGINAL FLUIDS IN OESTRUS AND SILENT OESTRUS BUFFALOES - S. Sathishkumar; Cecilia Joseph; T. Sarath; T.M.A. Senthilkumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Buffaloes have high productive potential but poor manifestations of oestrus signs and silent oestrus act as a major constraint in buffaloes affecting their reproduction. There are several detection tools used for detection and confirmation of oestrus in cattle but none of the methods have succeeded to overcome the problem of silent estrus in buffaloes. In recent years proteomics approach has gained much attention to identify proteins associated with various physiological and disease conditions in saliva and cervico vaginal fluid mostly in humans and up to certain extent in cattle and buffaloes. In this study twelve pluriparous Murrah buffaloes aged 4 to 7 years with good body condition were selected and divided into group I (regular oestrus), group II (silent oestrus). Each group carries six animals and saliva was collected at proestrus (day -3), oestrus (day 0) and diestrus stage (day 7). Cervico vaginal fluid (CVF) was collected only at oestrum stage. Protein profiling of saliva were studied by SDS - PAGE analysis. The SDS-PAGE analysis showed proteins of molecular weight 150, 110, 80, 40 kDa during proestrus; 150, 120, 70 and 50 kDa during oestrus; 250, 150, 90, 50 and 37 kDa during diestrus in group I buffaloes. Similarly, proteins of molecular weight 250, 150, 100, 80 and 25 kDa during proestrus; 150, 100, 75 and 50 kDa during oestrus and 250, 100,75 and 25 kDa during diestrus were observed  in group II buffaloes. The SDS-PAGE analysis of CVF showed proteins of molecular weight of 100 and 75 kDa in group I buffaloes and 250 and 150 kDa in group II buffaloes. Oestrus specific proteins with different molecular weights were identified in terms of different bands size. However further study is warranted to find out their role during oestrus in regular and silent oestrus buffaloes for the development of specific diagnostic assay.